Kualitas Mikrobiologis Susu Kambing dengan Metode Pasteurisasi High Temperature Short Time (HTST) pada Penyimpanan Berbeda - V. Wanniatie; A. Qisthon; A. Husni; E. Olsen (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2021)
The aim of this study was to determine the effectiveness of the pasteurization method on the microbiologicalquality of goat’s milk stored at different times in the refrigerator. The research was conducted in MarchMay 2020 at the Animal Production Laboratory of the University of Lampung and the Laboratory ofthe Lampung Veterinary Center. The goat milk sample were colleted from Etawah Grade goats fromsmallholder farms in Metro City. Milk samples were taken from 20 goats from Etawah Grade in the 2ndand 3rd lactation periods. The goat milk sample used was 9 liters. Goat milk samples were pasteurizedusing the high temperature short time (HTST) method at a temperature of 72ºC for 15 seconds thencooled and put in a plastic bottle and stored in the refrigerator. This study used a completely randomizeddesign (CRD) with long storage treatment (0 days, 12 days, 24 days, 36 days, 48 days, and 60 days) in therefrigerator. The results showed that pasteurized goat milk with different storage times had no effect onthe microbiological quality, namely TPC, S. aureus, coliform bacteria, E. coli, reductase numbers andpH values. The conclusion of this study is that pasteurized goat’s milk using the HTST method is stillsuitable for consumption until the 60th storage day